Mapping of alpha- and beta-globin genes on Antarctic fish chromosomes by fluorescence in situ hybridisation - PISANO, EVA; GHIGLIOTTI, LAURA; E. COCCA; F. MAZZEI; G. di PRISCO; H.W. DETRICH III; C. OZOUF COSTAZ (Kluwer Academic Publishers, 2003)
The pathways and mechanisms of genomic change that have led to the peculiar haemoglobinless phenotypeof the white-blooded Antarctic ice¢shes (16 species in the family Channichthyidae) constitute an important model for understanding the rapid diversification of the Antarctic notothenioid fish flock. To provide complementary structural information on genomic change at globin-gene loci in Antarctic fish species,cytogenetic studies and in-situ chromosomal mapping have been undertaken. Using a DNA probe containing one a- and one b-globin gene from the embryonic/juvenile globin gene cluster of the red-blooded species Notothenia coriiceps, we mapped the cluster on the chromosomes of Antarctic teleosts by fluorescence in-situ hybridization. As anticipated on the basis of its molecular organization, the cluster was located on a single chromosome pair in all of the red-blooded fish species probed (N. coriiceps, N. angustata, Trematomus hansoni, T. pennellii). In contrast, the a/b-globin probe did not recognize complementary sequences on the chromosomes of the white-blooded species Chionodraco hamatus and Channichthys rhinoceratus. These results represent the first example of chromosomal mapping of embryonic/juvenile globin genes in teleostean fishes. Beyond its relevance to the evolutionary history of Antarctic notothenioids, this work contributes to our understanding of the evolution of the chromosomal loci of globin genes in ¢shes and other vertebrates.